Dinamika Hukum Administrasi Negara Terhadap Mekanisme Kontinuitas Kebijakan di Masa Peralihan Kekuasaan Presiden - Firdaus Arifin (Jurnal Interpretasi Hukum, 2024)
Transitions of presidential powers often create policy uncertainty, which can disrupt the stability of the administration of government and violate the principle of legal certainty. State administrative law, as the main instrument in maintaining policy stability, has not been fully effective in ensuring policy continuity in Indonesia during the transition of power. The study aims to analyze the role of state administrative law in maintaining the continuity of public policy during the presidential transition of power. Using normative legal research methods, the study analyzed various regulations, such as Law Number 30 of 2014 on Government Administration, as well as conducting comparative studies with administrative legal systems in the United States and Germany. The results show that, despite efforts to provide a clear legal foundation for policy continuity, implementation on the ground is still weak, especially in terms of oversight and policy evaluation procedures. Countries such as the United States and Germany have succeeded in creating systems that allow policy continuity during the transition of power through stronger oversight mechanisms and transparent evaluations. The implication of this study is the need to reform administrative law in Indonesia, by adding more specific regulations to ensure policy stability and protect public interests during the transition of power.